2007
DOI: 10.3327/jnst.44.894
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase Flow Patterns in a Four by Four Rod Bundle

Abstract: Air-water two-phase flow patterns in a four by four square lattice rod bundle consisting of an acrylic channel box of 68 mm in width and transparent rods of 12 mm in diameter were observed by utilizing a high speed video camera, FEP (fluorinated ethylene propylene) tubes for rods, and a fiberscope inserted in a rod. The FEP possesses the same refractive index as water, and thereby, whole flow patterns in the bundle and local flow patterns in subchannels were successfully visualized with little optical distorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…In Fig. 8, the measured transition from bubbly to bubble-churn flow located on the left side of bubbly to churn flow developed by Mizutani et al (2007). In contrast to the observation of Mizutani et al, bubblechurn flow patterns were not observed in the present experiments because the churn flow of gas-liquid flow was more stable than the churn flow in the heated channel.…”
Section: Comparisons With Existing Flow Pattern Maps and Criteriacontrasting
confidence: 85%
See 3 more Smart Citations
“…In Fig. 8, the measured transition from bubbly to bubble-churn flow located on the left side of bubbly to churn flow developed by Mizutani et al (2007). In contrast to the observation of Mizutani et al, bubblechurn flow patterns were not observed in the present experiments because the churn flow of gas-liquid flow was more stable than the churn flow in the heated channel.…”
Section: Comparisons With Existing Flow Pattern Maps and Criteriacontrasting
confidence: 85%
“…Herná ndez et al (2011) found a similar result. When the superficial liquid velocity j l was greater than 0.2 m/s, the transition boundary of annular flow in this experiment corresponds to the flow pattern transition boundary reported by Mizutani et al (2007).…”
Section: Comparisons With Existing Flow Pattern Maps and Criteriamentioning
confidence: 55%
See 2 more Smart Citations
“…Figure 4 shows flow patterns in the rod bundle. Flow patterns were classified into six regimes shown in Table1 based on the authors' previous study (10) . The flow is bubbly at low J G as shown in Fig.…”
Section: Journal Of Power and Energy Systemsmentioning
confidence: 99%